A novel glucomannan incorporated functionalized carbon nanotube films: Synthesis, characterization and antimicrobial activity. (1st October 2020) - Wang, Lin; Lin, Lizhuan; Pang, Jie
Graphical abstract: Highlights: The film containing CKGM and GL were reinforced with functionalized carbon nanotube. Physicochemical and mechanical properties of nanocomposite films were investigated. Mechanical and barrier properties of the film enhanced with PCNT incorporation. The 80PCNT@CKGM/GL nanocomposite film displays desirable antibacterial ability. Abstract: A novel nanocomposite film was developed by incorporating functionalized carbon nanotube (PCNT) and gallic acid (GA) into carboxymethyl konjac glucomannan (CKGM) and gelatin (GL) matrix. The influences of the PCNT content on the structural, morphological, mechanical, barrier, thermal and antimicrobial properties of CKGM/GL nanocomposite film were discussed. The structure of PCNT@CKGM/GL nanocomposite film was characterized by FT-IR, SEM, and AFM. The crystal structure and thermal ability of the film were generated by XRD and TGA-DTG. The analyses of FT-IR revealed that the amide linkage and strong hydrogen bonding were formed between CKGM, GL, and PCNT. Moreover, the characterization of mechanical properties, moisture barrier, and antimicrobial activities indicated the benefits of adding PCNT into CKGM/GL films. The results suggested that the PCNT@CKGM/GL films exhibited antimicrobial activity against Staphylococcus aureus and Escherichia coli . Therefore, such antimicrobial nanocomposite films have the potential of maintaining the quality and prolong the shelf life of food products.